Language, culture, and identity signs of life - Sinha, Vera da Silva; Moreno-Núñez, Ana; Tian, Zhen, (Linguist) (Cognitive linguistic studies in cultural contexts ;, 2020)
"The dynamics of language, culture and identity are a major focus for many linguists and cognitive and cultural researchers. This book explores the inextricable connection that language has with cultural identity and cultural practices, with a particular emphasis on how they contribute to shaping personal identity. The volume brings together selected peer-reviewed papers from the 7th International Conference on Language, Culture and Mind held at Hunan University, 2016, with other specially commissioned chapters. Like the conference, this book aims to enhance mutual understanding among researchers from diverse disciplinary and theoretical perspectives, offering a wealth of insights to a wide range of readers on recent culturally oriented cognitive studies of language"--